Long-Term Follow-up of Arthrodesis vs Total Joint Arthroplasty for Hallux Rigidus. (April 2017) - Stone, Oliver D.; Ray, Robbie; Thomson, Colin E.; Gibson, J. N. Alastair
Background: The optimal operative management of hallux rigidus is still a matter for debate among surgeons. Despite arthrodesis widely considered to be the gold standard treatment, many surgeons advocate arthroplasty as a suitable alternative. There are, however, few long-term or high-quality studies evaluating these modalities. We present the 15-year follow-up of a randomized controlled trial. Methods: This data is the follow-up to the original study published in 2005. In the original study, 63 patients (77 toes) were recruited to and randomized to have either metatarsophalangeal joint (MTPJ) arthrodesis or arthroplasty. The primary outcome measure was a decrease in pain on a visual analog scale (VAS) at 24 months. In the present study, data were available for all surviving patients (52 patients, 66 toes). Data were collected in the form of satisfaction scores, VAS for pain, the VAS foot and ankle and survivorship data. Results: The results of the original study demonstrated that pain relief was greater following arthrodesis at 2 years. At 15 years, patients with an arthrodesis experienced less pain and were more satisfied compared to those with an arthroplasty. No functional differences were seen between these 2 groups. There were more revisions in the arthroplasty group. Conclusion: Despite the hope of better function, less pain, and greater satisfaction from MTPJ replacement, this was not found in our patient population. The long-term results of our study showed that arthrodesis outperformed arthroplasty. If an arthroplasty failed, then salvage was likely to be technically difficult, with significant potential for complications. Level of Evidence: Level I, randomized controlled trial.